Asociación Colonia Española de Nuevitas. : Apuntes sobre su fundación. (Revista de História Regional, 2025)
The study of the rural world is essential to enrich local, regional and national historiographies. Rural areas are characterized by the predominance of agricultural activities, typical of these areas, such as small and artisanal industries, as well as some aspects of daily life that impacted social activities. The study of Hispanic immigrants settled in the Nuevitas region, as well as the sociability they developed during the first years of the 20th century in Cuba. These are aspects to be unraveled in order to achieve a better understanding of rural areas; a space that during these years will witness a slow transition where rural, port and industrial environments will coexist until the second decade of the 20th century.This research is carried out to study the sociability of Hispanic immigrants settled in the Nuevitas region in the early years of the 20th century. Given the scientific problem of how the Colonia Española de Nuevitas association emerged in 1903, assuming the Colonia Española de Nuevitas association as the object of study. With the aim of determining the founding process of the Colonia Española de Nuevitas association in 1903.The association was created in response to the need of Spanish immigrants settled in the territory to feel publicly represented as an entity with a collective expression of their idiosyncrasy in the face of the nascent Republic of Cuba. Some founders, merchants and owners, are the fundamental drivers of the association and its optimal performance in services.
Keywords: Nuevitas. Spanish immigrants. Association. Sociability. Regional history.